- Impact of business incubators on cost reduction by supporting entrepreneurship for small businesses - Comparative applied study - Al Kenzi, Saber Taj Alsar Mohammad Abdul Rahman; Taha, Mohamed El Mahdi Mostafa (Journal of Economic, Administrative and Legal Sciences, 2018)
The problem of the study was to reduce the financing and marketing costs of small projects sponsored by business incubators in order to achieve the desired goal of partial revenue and continuity. . The study aimed to demonstrate the impact of business incubators in creating the competitive advantage of small enterprises and their role in supporting the national economy assuming that lowering costs achieves the competitive advantage of small businesses. The results have resulted in the significant impact of business incubators and entrepreneurship in reducing financing costs, marketing expenses and the cost of franchising. The study recommended expanding and paying attention to small projects and supporting innovations and successful ideas in order to support the national economy and fight unemployment.